Myroides injenensis Bacteremia and Severe Cellulitis. (17th June 2019) - LaVergne, Stephanie; Gaufin, Thaidra; Richman, Douglas
Abstract: Myroides spp. are environmental bacterial organisms that rarely cause disease in humans. Myroides spp. infections are infrequently reported in the literature, and Myroides injenensis infections are quite uncommon. Myroides spp. usually infect immunocompromised hosts and can have highly resistant antibiotic susceptibility patterns. Here we report a case of Myroides injenensis bacteremia and severe cellulitis in a patient with cirrhosis and review the literature of other Myroides spp. infections.